Institutional theory - Lawrence, Thomas B.; Shadnam, Masoud (My University, 2008)
Institutional theory is a theoretical framework for analyzing social (particularly organizational) phenomena, which views the social world as significantly comprised of institutions - enduring rules, practices, and structures that set conditions on action.
Keywords: organizational communication